Pengembangan LKPD Pembuatan Briket Kulit Kakao sebagai Bahan Ajar Siswa SMA - Septianti, Indri; Carolina, Hifni Septina (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2023)
Cocoa waste that is not handled seriously will cause environmental problems such as an unpleasant odor. Cocoa waste will have a significant role if used as alternative energy, namely briquettes. Utilization of cocoa shells into briquettes can be developed into LKPD teaching materials. This study aims to produce worksheets for making cocoa shell briquettes as teaching materials for high school students. The research method used is the research and development method (Research and Development/R&D). The results of the research that has been done show the feasibility of LKPD according to material experts and media experts. Material validation was carried out twice, so that an average score of 45 was obtained with a percentage of 90% and included in the